THE IMPACT OF TEACHING TOPICAL STRUCTURE ANALYSIS ON WRITING PERFORMANCE OF TURKISH EFL SPEAKERS - Çepni, Gökhan; Bada, Erdoğan (PEOPLE: International Journal of Social Sciences, 2019)
As coherence is abstract in nature and there are very few practical techniques to teach it, this is considered to be one of the main problems that EFL students and teachers encounter. Although there is considerable research analyzing problems and difficulties with coherence among EFL learners, few practical pedagogical strategies have been suggested that can be used by teachers and understood by learners. Topical Structure Analysis is one of such techniques suggested and could be taught to EFL learners in order to help them improve their writing skills. This experimental study sheds light on the effects of teaching Topical Structure Analysis to Turkish university students who learn English as a foreign language. Two groups with four participants in each were used for this research. While one group was subjected to Topical Structure Analysis treatment (experimental group) for six weeks, the other received no such training. At the end of such a training period, both groups were assigned writing tasks which were analyzed for coherence. The results obtained indicate that a considerably positive effect of teaching Topical Structure Analysis was observed on the writings of experimental group, while the participants of the control group remained relatively poor performers of coherence in their writings.